Polymorphism and metal-induced structural transformation in 5, 5′-bis(4-pyridyl)(2, 2′-bispyrimidine) adlayers on Au(111). Issue 23 (31st May 2018) - Hötger, Diana; Carro, Pilar; Gutzler, Rico; Wurster, Benjamin; Chandrasekar, Rajadurai; Klyatskaya, Svetlana; Ruben, Mario; Salvarezza, Roberto C.; Kern, Klaus; Grumelli, Doris
Abstract : Addition of iron to a self-assembled molecular network can lift polymorphism and leads to the expression of one single metal–organic structure on a surface. Abstract : Metal–organic coordination networks self-assembled on surfaces have emerged as functional low-dimensional architectures with potential applications ranging from the fabrication of functional nanodevices to electrocatalysis. Among them, bis-pyridyl-bispyrimidine (PBP) and Fe-PBP on noble metal surfaces appear as interesting systems in revealing the details of the molecular self-assembly and the effect of metal incorporation on the organic network arrangement. Herein, we report a combined STM, XPS, and DFT study revealing polymorphism in bis-pyridyl-bispyrimidine adsorbed adlayers on the reconstructed Au(111) surface. The polymorphic structures are converted by the addition of Fe adatoms into one unique Fe-PBP surface structure. DFT calculations show that while all PBP phases exhibit a similar thermodynamic stability, metal incorporation selects the PBP structure that maximizes the number of metal–N close contacts. Charge transfer from the Fe adatoms to the Au substrate and N–Fe interactions stabilize the Fe-PBP adlayer. The increased thermodynamic stability of the metal-stabilized structure leads to its sole expression on the surface.